Public debt in new EU member states – Panel data analysis and managerial implications - Mario Pečarić; Vlado Slišković; Tino Kusanović (Management : Journal of Contemporary Management Issues, 2018)
The paper argues that it is impossible to resolve the public debt problem within the existing economic policy model without changing the conceptual relationship between monetary and fiscal policy, i.e. without reconfirming the relationship between the policies and without strengthening the fiscal policy role. Otherwise, it is believed, the current model leads to a recession, while public debt problem remains unresolved. The existing model does not question the creation and structure of private debt and its effects on public debt, but the attention is given only to irresponsible fiscal policy. Understanding the public debt determinants is a prerequisite for effective public debt management and for private agents’ positive expectations. In the paper, several managerial implications of the research results are, also, identified and presented.